One-Pot Synthesis of Guanidinium 5,5′-Azotetrazolate Avoiding Isolation of Hazardous Sodium 5,5′-Azotetrazolate - Labaj, Miroslav; Jalový, Zdeněk; Matyáš, Robert; Nesveda, Jiri; Mikuláštík, Jakub; Votýpka, Adam (American Chemical Society, 2024)
Sodium 5,5 '-azotetrazolate (Na2AzT) is a starting material for various azotetrazole salts that find applications as lead-free primary explosives or high-nitrogen compounds for inflating safety systems (in particular, guanidinium azotetrazolate, GZT). Sodium azotetrazolate, after preparation, is commonly isolated as the pentahydrate, which is relatively safe for handling. But it readily loses hydrate water molecules at higher temperatures or by treatment with organic solvents. In such cases, sensitivity to mechanical stimuli increases considerably and explosion accidents may occur. In this work, the thermal conditions and the role of solvents in water loss from sodium 5,5 '-azotetrazolate pentahydrate are presented. Impact and friction sensitivity parameters of the products are described. In the case of guanidinium azotetrazolate, the process for its preparation without producing sodium 5,5 '-azotetrazolate is introduced, thus avoiding manipulation of hazardous material and increasing the safety of the procedure.
Syntéza guanidinium-azotetrazolátu v jednom kroku bez isolace nebezpečného azotetrazolátu sodného
Keywords: sodium azotetrazolate; guanidinium azotetrazolate; improved synthesis; sensitivity to impact and friction; azotetrazolát sodný; guanidinium-azotetrazolát; syntéza; citlivost k nárazu a tření